REFERENT LANGUSNG, TAK LANGSUNG, GAIB, DAN PLESETAN (Kajian Pengembangan Teori Ferdinand de Saussure) - Idrus Ahmad (Fakultas Ilmu Budaya, Universitas Jambi, 2021)
Referent or reference to the meaning of a word is hardly discussed in detail by linguists after Ferdinand de Saussure. The reason is because the meaning of the word is very dynamic or raises the possibility of various meanings. Another reason, there are referents who are not in the real world but in the shadow or fantasy. Therefore, this study is a form of developing reference theory into direct, indirect, occult, and play referent referents. The analytical method used in this study is a qualitative descriptive method. Meanwhile, the collection technique used is a documentation study, which is collecting writings related to the object of research, namely word studies as one of the elements in the linguistic field, followed by reading techniques. Reading is done to: (1) understand the overall content of the data sources used in this study; (2) sharpen previous understanding; (3) understand the focus of the research, namely the word described by linguist Ferdenand de Saussure. Data analysis techniques in this study include: (1) data reduction as a selection process, focusing attention on simplification, abstracting, and transformation of rough data, obtained from various written records. Reports or data obtained are stated in the form of a complete and detailed description of the referent as one element of the meaning of the word.